When will civil society sanction the state? Evidence from Mali - Bleck, Jaimie; Gottlieb, Jessica; Kosec, Katrina (International Food Policy Research Institute, 2023)
Under what conditions will civil society organizations (CSOs) sanction corruption (the private use of public funds)? CSOs have overcome coordination problems, but could either use this capacity to hold government accountable for public goods provision or to extract rents from politicians. We develop a model and test its predictions using a face-to-face survey with 1,014 CSO leaders from 48 communes in Mali. We describe a forthcoming performance-based funding program (PBF) providing a formal channel for civil society monitors to sanction mayoral corruption: they influence whether or not mayors receive a performance bonus. We ask CSO leaders their likelihood of sanctioning known corruption under the program and their expected transfer price if they instead enter into a collusive bargain. We find that CSOs most embedded in the community are best able to extract informal transfers from the mayor and least likely to sanction. By contrast, CSOs with high technical and informational capacity are most likely to sanction.